STATISTICAL SURVEY OF MIGRATION PROCESSES IN UKRAINE IN CONDITIONS OF EUROPEAN INTEGRATION - Klimova, Inna; Nikodyuk, Snizhana (Zhytomyr Ivan Franko State University, 2019)
The article is devoted to the study of the main indicators of the Ukrainian labor market and the phenomenon of labor migration to the countries of the European Union and the world in general. The peculiarity of this situation and migration policy in our country consists in Ukraine acting simultaneously as the country of origin, destination and transit of migrants. On the one hand, this leads to many problems occurring, on the other hand, it is opening up new opportunities related to migration.The basis of our research was the official statistics of the country's population movements. The analysis of supply and demand in the labor market showed that the supply level was drastically increased. However, the availability of vacancies allows us to state the dissatisfaction of potential employees with those because of their allowance. The structure of unemployment among various professional groups was also investigated.We analyzed the directions, age groups and employment sectors of Ukrainian labor migrants. Moreover, we looked into the financial income of workers from the major labor donor countries. We discovered that the top three countries of labor migration are the Philippines, Pakistan and Ukraine. According to the results of the study of financial revenues, it is found that long-term migrants' transfers to Ukraine make up almost half of the households’ budget.It has also been ascertained that the uncontrolled arrival of workers from abroad increases competition in the national labor market, which may cause a decrease in real wages and an increase in unemployment. Illegal staying of foreigners, and especially them working here, provokes the development of criminal structures, undermining the legal system. Also, foreign migrants who are not cared for by their native country can become an additional burden on the host country's social system.